OPTIMALISASI LETTER OF COORDINATION AGREEMENT TERKAIT KOORDINASI ANTARA UNIT TOWER DAN AIRLINES TERHADAP NAVIGASI PENERBANGAN DI PERUM LPPNPI AIRNAV INDONESIA UNIT NUNUKAN - B. Lucky Wahyudi Lukman; Ade Irfansyah; Ramining Puspitaningsih (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This final proect study examines the provision od information about flightplan data provided by airlines to tower units. Airlines do not provide aircraft data information in a timely and correct manner, this result in a breakdown of coordination. The author compiled this final project in order to be able to examine the LOCA between Airlines and the Nunukan tower unit. So that the provision of air traffic service can run effectively and efficiently whitout forgetting the safety aspect. Changs in LOCA in the coordination between units by not changing or violating the highest rules (ICAO Annex) This final proect research uses a qualitative descriptive research desighn that uses 2 variable, namely; Optimizing LOCA between tower and airlines units (variable X) and on the Effectivennes of Flight Navigation Service at Nunukan Unit (variable Y). Data collection techniques using; observation, literature study. The result o the data obtained and the analysis o problem, the result of the data obtaidef can be concluded that the need for urther developtmen o the optimization of LOCA between towe and airlines units in the Nunukan unit to improve the effectiveness o providing light navigation service . Te solution to te problem that is considered the most appropriate according to the authoe is to review the LOCA tower unit and airlines to add delegation of air traffic communication so that coordination becomes more effective.